Allosteric Modulation and Accelerated Resensitization of Human P2X3 Receptors by Cibacron Blue - Alexander, Karen; Niforatos, Wende; Bianchi, Bruce; Burgard, Edward C.; Lynch, Kevin J.; Kowaluk, Elizabeth A.; Jarvis, Michael F.; van Biesen, Tim (The Journal of pharmacology and experimental therapeutics, 1999)
The activity of ATP as a fast neurotransmitter is mediated by the P2X family of ligand-gated ion channels. P2X receptor subtypes are subject to functional modulation by a diverse set of factors, including pH, divalent cations, and temperature. The human P2X3(hP2X3) receptor subunit is expressed primarily in sensory ganglia where it exists as either a homomultimeric receptor or, in combination with P2X2, as a heteromultimeric receptor. This article describes the allosteric modulatory effect of the putative P2X receptor antagonist cibacron blue on the activity of recombinant hP2X3 receptors. In 1321N1 cells expressing the hP2X3 receptor, cibacron blue mediated a 3- to 7-fold increase in both the magnitude and the potency of ATP-activated Ca2+ influx and transmembrane currents. The half-maximal concentration of cibacron blue required to mediate maximal potentiation (EC50 = 1.4 μM) was independent of the agonist used to activate the hP2X3 receptor. The nonselective P2 receptor antagonist PPADS (pyridoxal-5-phosphate-6-azophenyl-2′,4′-disulfonic acid) caused a rightward shift of the cibacron blue concentration-effect curve, whereas increasing concentrations of cibacron blue attenuated PPADS antagonism. In addition to potentiating the effects of ATP at the hP2X3 receptor, cibacron blue also produced a 6-fold increase in the rate of hP2X3receptor recovery from desensitization (from T1/2 = 15.9 to 2.6 min), as evidenced by its ability to restore ATP responsiveness to acutely desensitized receptors. Consistent with the properties of other ligand-gated ion channels, these results suggest that hP2X3 receptor activity can be allosterically modulated by a ligand distinct from the endogenous agonist.